The Effect of Emotional Intelligence and Workload on Employee Work Productivity at Pt Astra International Tbk – Daihatsu Sales Operation in Sleman - Mahadewi Kurnia Putri; Dwi Utami Puterisari (Jurnal Manajemen dan Profesional, 2026)
This study examines the effects of workload and emotional intelligence on employee productivity at PT Astra International Tbk - Daihatsu Sales Operation. A quantitative approach with saturation sampling yielded 57 respondents. Multiple linear regression analysis using IBM SPSS revealed that workload has a positive and significant impact on productivity, while emotional intelligence shows a positive but statistically insignificant effect. The simultaneous F-test confirms that both variables jointly exert a significant influence on productivity. These findings underscore the need for organizations to balance effective workload management and emotional competence to achieve optimal employee performance.